Rules of Indices .

Algebra Level 2

Simplify it and write the solution .

[ x b x c ] ( b + c a ) × [ x c x a ] ( c + a b ) × [ x a x b ] ( a + b c ) \left[ \cfrac { x^{ b } }{ x^{ c } } \right] \overset { (b+c-a) }{ } \times \quad \left[ \frac { x^{ c } }{ x^{ a } } \right] \overset { (c+a-b) }{ } \times \quad \left[ \frac { x^{ a } }{ x^{ b } } \right] \overset { (a+b-c) }{ }


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Noel Lo
May 30, 2015

The power works out to be:

(b-c)(b+c-a) + (c-a)(c+a-b) + (a-b)(a+b-c)

= b^2 - c^2 -a(b-c) + c^2 -a^2 - b(c-a) + a^2 - b^2 - c(a-b)

= -a(b-c) -b(c-a) - c(a-b) = -ab + ac -bc + ab - ca + bc = 0

x^0 = 1 unless x=0.

E x p . = X b ( b + c a ) + c ( c + a b ) + a ( a + b c ) X c ( b + c a ) + a ( c + a b ) + b ( a + b c ) = X a 2 + b 2 + c 2 X a 2 + b 2 + c 2 = 1 Exp. = \dfrac{X^{b(b+c-a) + c(c+a-b) +a(a+b-c)} }{X^{c(b+c-a) +a(c+a-b) +b(a+b-c)} } \\ =\dfrac{X^{a^2+b^2+c^2}}{X^{a^2+b^2+c^2}} \\=1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...